Morphological characterization of the nasopalatine region in human fetuses and its association to pathologies - Saulo Gabriel Moreira FALCI; Flaviana Dornela VERLI; Alberto CONSOLARO; Cassio Roberto Rocha dos SANTOS (University of São Paulo, 2013)
The nasopalatine region is composed of structures such as the vomeronasal organ and nasopalatine duct. The nasopalatine duct may provide the communication of the mouth to the nasal cavity in human fetuses and can be obliterated in an adult human. Knowledge on the development of the nasopalatine region and nasopalatine duct in humans is necessary for understanding the morphology and etiopathogenesis of lesions that occur in this region. Objective The aim of the present study was to describe the morphological aspects of the nasopalatine region in human fetuses and correlate these aspects with the development of pathologies in this region. Material and Methods Five human fetuses with no facial or palatine abnormalities were used for the acquisition of specimens from the nasopalatine region. After demineralization, the specimens were histologically processed. Histological cuts were stained with methylene blue to orient the cutting plane and hematoxylin-eosin for the descriptive histological analysis. Results The age of the fetuses was 8.00, 8.25, 9.00 and 9.25 weeks, and it was not possible to determine the age in the last one. The incisive canal was observed in all specimens as an opening delimited laterally by the periosteum and connecting oral and nasal cavity. The nasopalatine duct is an epithelial structure with the greatest morphological variation, with either unilateral or bilateral occurrence and total patent, partial patent and islet forms. The vomeronasal organ is a bilateral epithelized structure located alongside the nasal septum above the incisive canal in all the fetuses. Conclusions The incisive canal, nasopalatine duct and vomeronasal organ are distinct anatomic structures. The development of nasopalatine duct cysts may occur in all forms of the nasopalatine duct.